# 3 Answers

solve for y: 3y-2(y-1)/6=-1

3y - 2y +2/6 = -1

y + 1/3 = -1

y = -1 1/3

# solve for y: 3y-2(y-1)/6=-1

3 (-1 1/3) - 2(-1 1/3) +2 /6 = -1

-4 + 2 2/3 + 2/6 = -1

-1 1/3 + 1/3 = - 1

7 years ago. Rating: 1 | |

Check my answer: Did I do this right?

I agree! I worked the problem the way you did it first. Then worked it the other way. The divided by 6 (how it's written) got me confused.

# 3y-2(y-1)/6=-1

3y - __(2y - 2)__ = -1

6

3y - 1/3y + 1/3 = -1

9/3y - 1/3y + 1/3 = -1

8/3y + 1/3 = -1

8/3y + 1/3 - 1/3 = -1 - 1/3

-3/3 - 1/3 = - 4/3

8/3y = -4/3

8/3 / 8/3 = -4/3 * 3/8

y = -1/2

7 years ago. Rating: 1 | |

I would trust your answer more than mine, and I wonder if the whole thing should be divided by 6? That would make it:

1y + 2 / 6 = -1

1/6y + 1/3 = -1

y + 2 = -6

y = -4

(The way the division is added in at the end is where I get messed up.) I'll check with someone who knows and get back to you.... your answer looks good to me, but so do both of mine. :o

1y + 2 / 6 = -1

1/6y + 1/3 = -1

y + 2 = -6

y = -4

(The way the division is added in at the end is where I get messed up.) I'll check with someone who knows and get back to you.... your answer looks good to me, but so do both of mine. :o